Mental pain and pain-proneness in patients with migraine: results from the PAINMIG cohort-study. (25th October 2021) - Cosci, Fiammetta; Svicher, Andrea; Mansueto, Giovanni; Benemei, Silvia; Chiarugi, Alberto; De Cesaris, Francesco; Guidi, Jenny; Zipfel, Stephan
Abstract: Background: Pain has been qualified under four categories: nociception, perception of pain, suffering, and pain behaviors. Most of the literature on migraine has devoted attention to the first two. The aim of the present cohort study was to investigate patients with migraine enrolled at a tertiary care unit to study suffering and mental pain and identify potential risk factors for migraine. Methods: An observational cross-sectional study was carried out on patients with chronic migraine (CM) and episodic migraine (EM), and healthy subjects (HS). The three groups were matched for age and sex. A comprehensive assessment of migraine disability, pain, psychiatric disorders, psychosomatic syndromes, depressive and anxious symptoms, euthymia, psychosocial variables, mental pain, and pain-proneness (PP) was performed. Results: Three hundred subjects were enrolled (100 CM, 100 EM, and 100 HS). Based on the multiple regression analyses, those presenting PP (social impairment: odds ratio [OR] = 3.59, 95% confidence interval [CI] = 1.14-11.29; depressive symptoms: OR = 3.82, 95% CI = 1.74-8.41) were more likely to be CM than HS. Those with higher levels of PP (social impairment: OR = 4.04, 95% CI = 1.60-10.22; depressive symptoms: OR = 2.02, 95% CI = 1.26-3.24) were more likely to be EM than HS. Those presenting higher levels of mental pain were more likely to be CM than EM (OR = 1.45, 95% CI = 1.02-2.07). Conclusion: Migraine is an unpleasant sensory and emotional experience associated with psychosocial manifestations that might contribute to the level of suffering of the individuals. Mental pain resulted to be the variable that most differentiated patients with CM from EM.